2022
DOI: 10.1021/acsanm.2c01346
|View full text |Cite
|
Sign up to set email alerts
|

Peptide-Inspired One-Step Synthesis of Surface-Functionalized Fe3O4 Magnetic Nanoparticles for Oriented Enzyme Immobilization and Biocatalytic Applications

Abstract: Immobilization of enzymes on magnetic nanoparticles (MNPs) is an effective way to ensure their recycling. However, MNPs are usually prepared and modified step by step before immobilization as the conditions are too harsh to maintain the three-dimensional structures and functions of the target enzymes. Herein, peptide-inspired magnetic nanocomposites (K5C@Fe3O4) were mildly prepared, where the proteins in the composites could functionalize efficiently for immobilization of the target dual enzymes without prior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Moreover, our proposed encapsulating strategy may avoid the problems that arise from unfavored orientations of enzymes bound directly to MNPs. This last approach has faced challenges in terms of substrate accessibility and the extent of enzyme remote activation. Consequently, an encapsulation method may provide versatility and even expand the range of therapeutic enzymes that can be remotely activated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, our proposed encapsulating strategy may avoid the problems that arise from unfavored orientations of enzymes bound directly to MNPs. This last approach has faced challenges in terms of substrate accessibility and the extent of enzyme remote activation. Consequently, an encapsulation method may provide versatility and even expand the range of therapeutic enzymes that can be remotely activated.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the RFP-SpyCatcher loadings on MNPs were 14.9 ± 0.3 μg-protein/mg-MNP and 16.2 ± 0.1 μg-protein/mg-MNP, respectively. In comparison, it was reported that SpyCatcherfunctionalized MNPs had a loading of 0.7 μg-enzyme/mg-MNP in a previous study that used Spy chemistry for enzyme co-immobilization from cell lysates, 34 suggesting the high loading capacity of our platform for protein co-immobilization from cell lysates. Notably, each protein loading on MNPs accounted for 75−90% of those achieved from co-immobilization using pure proteins, suggesting the high efficiency of the MNP platform to co-immobilize two different proteins from cell lysates in a one-pot system.…”
Section: High Specificity Of Spytag-functionalized Mnps To Conjugate ...mentioning
confidence: 74%
“…31,33 More recently, immobilization of dual SpyTagfused enzymes on SpyCatcher-functionalized MNPs from cell lysates has been reported. 34 However, the enzyme loading was low (∼0.7 mg/g) and the ratio of each enzyme loading on MNPs could not be tuned because two enzymes were fused to the N and C termini of one SpyTag. Also, the materials reported in the study were prone to aggregation, which limits their colloidal stability in high ionic strength solutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Feng and co-workers 51 used 3-(aminopropyl)triethoxysilanecoated MNPs to immobilize aminoacylase, and the immobilized enzymes exhibited more favorable thermal and pH stability than the free enzymes. Zhou et al 52 immobilized dual enzymes onto peptide-inspired MNPs, enhancing their thermal stability.…”
Section: Introductionmentioning
confidence: 99%